Revealing the Value of Religious Tolerance Based on Social Interaction Among Students of Public Junior High Schools 1 and 3 Tosari in Pasuruan Regency - Avisena, Ahmad; Ch, Mufidah; Ali, Nur (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2025)
Cases of religious intolerance in the education sector in Indonesia are still common. Tosari District has a diverse religious population, but it is known that religious conflicts rarely occur, especially in the field of education, where massive social interaction can foster harmony between religious communities. This study aims to explain and compare religious tolerance values based on social interaction at State Junior High Schools (SMPN) 1 and 3 in Tosari District, Pasuruan Regency. The researcher selected these two educational institutions due to their differing religious compositions. SMPN 1 Tosari has the highest number of Hindu students, while SMPN 3 Tosari is predominantly Muslim. This study employs a qualitative approach with a multiple case study design. The findings reveal three religious tolerance values in both institutions: mutual respect, social concern, and solidarity. These values emerge based on different patterns of social interaction. The study recommends strengthening religious tolerance values in junior high schools in general.